Secuenciación y análisis de dos genomas bacterianos; Thermus sp. 2.9 y Bacillus thuringiensis INTA Fr7-4 : identificación y análisis funcional de proteínas/enzimas con aplicación agroindustrial - Navas, Laura Emilce (2016)
Genome sequencing of native microorganisms represents a versatile tool to examine their\nbiodiversity and the exploitation of their genes in biotechnological applications. DNA sequencing of the complete genome of two bacterial isolates from Argentina was undertaken using next-generation technologies. The first one corresponds to a thermophilic bacterium of\nthe genus Thermus, whose interest is based on its thermophilic enzymes. From a genetic perspective, this isolate is close to Thermus aquaticus. Five enzyme-coding genes useful in many industrial applications were expressed in E. coli and the product of two of them, a phospholipase and a laccase were analysed functionally. Both enzymes showed optimal activity and thermostability at high temperatures. The other sequenced genome corresponds to an isolate of Bacillus thuringiensis, a species known for the production of insecticidal\ncrystals during sporulation. We obtained the complete sequence of a novel megaplasmid which includes 8 insecticidal genes of the cry and vip types, which are arranged in a pathogenicity island. Two cry8 genes were expressed separately in an acrystalliferous strain\nof B. thuringiensis, leading to the formation of ovoid crystals in the recombinant strains. The toxicity against larvae of Anthonomus grandis (Coleoptera) of one recombinant strain was\nsimilar to that of the native isolate.